Seasonal variation of parasitic infestation in perches from beel fisheries of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Seasonal variation of water quality parameters, parasitic infestation, clinical and histological observation of two endangered perches, Baila (Glossogobius giuris) and Colisa (Colisa fasciata) were investigated from two different beels namely, Kailla beel, Mymensingh and Noli beel, Kapasia, Gazipur during June, 2014 to May, 2015. Water quality parameters did not showed much variations except temperature which was minimum and ammonia values which were maximum during winter season. During observation, investigated fishes were highly infested by digeneatic trematode followed by cestode, acenthocephala, monogeneatic trematode and protozoan parasites. Maximum prevalence, mean intensity and abundance of parasites were observed in Baila from Colisa during winter season in both areas. Minimum level of infestation were recorded during summer season in both areas. Whereas, in rainy and autumn seasons average number of parasites were noticed. Clinically it was observed that, fishes were affected with parasitic infestation, EUS, gill rot, fin and tail rot, nutritional deformities, numerous red spots and white patches in lateral and ventral regions during winter season in both beels. Major pathology in the skin and muscle were loss of epidermis, epidermis separated from dermis, necrosis of myotoms, vaccums and hemorrhage. Loss of primary and secondary gill lamellae, hypertrophy, clubbing, presence of monogenetic trematodes and hemorrhage were found in gill. Marked melanomacrophages, severe haemorrage, vaccums, hepatocytic necrosis and fat droplets were found in liver. In kidney, numerous haemorragic areas, vaccums, fat droplets, coagulative necrosis and degenerated kidney tubules were seen especially in winter season. Whereas, in summer season, clinical and pathological condition of fishes gradually reduced to almost normal condition except few vaccums and hemorrhage in internal organs. Comparatively normal or reduced pathological sings in all the organs were observed in rainy and autumn seasons. Fishwise, Baila were more infested by parasites than Colisa. On the basis of sampling stations, perches of Kailla beel were more affected by parasites than perches of Noli beel.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 371-379